(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Filipinos have their own way for shining their shoes. They tend to use different routines for making their shoes looks brand new, presentable and fabulous to use with walking, boosting confidence to user. Lustra Zapatos is a company providing shoe cleaning cream that aims to provide the best satisfaction to its consumers through its innovative, organic and environment friendly and fulfilling services. The Lustra Zapatos will manufacture 100% natural and organic shoe polish and guarantees that there are no artificial colorants, lathering agents, synthetic additives, preservatives, petroleum products that is in valuable for those who suffer from chemical sensitivities. It is unique from its competitors because its ingredients are made from natural materials. The Lustra Zapatos is a partnership between four individuals working together to produce an affordable organic shoe polish products. The survey results affirmed that the aspects of the study, the marketing viability, concluded that the place of the business is accessible for the target market and is strategic for the business. After evaluating the significant factors in marketing, financial, product and services, the study is therefore recommended that organic shoe polish will pursue.There is a growing population of people who love to try new things. The researchers came up with the idea of introducing a shoe polish in the market which uses safe, environment-friendly and at the same time with natural ingredients. The business will be distributing its product with the help of a distributor-wholesaler and would be offering the product at a price below that of the average price of shoe polish in the market. Consequently the company will promote its business and its product line through advertising and other venue for its promotion.